THE CORRELATION BETWEEN BACKGROUND KNOWLEDGE AND MOTIVATION ON STUDENTS’ SPEAKING PERFORMANCE - mutmainah mutmainah mutmainah; Hamiddin Hamiddin Hamiddin; Febti Ismiatun (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
AbstractThis study aimed at knowing the correlation between students’ background knowledge and motivation on students’ speaking performance. Background knowledge here was students’ background knowledge of related topic. The research method was quantitative research in the form of multiple correlation design. There were 30-second semester students as the participants. The instruments were drama performance test, 9 items of background knowledge questionnaire adapted from Khabbazbashi (2014) and 30 items of motivation questionnaire adapted from Gardner (2004) to collect the data. The finding of the study revealed that there was no correlation between students’ background knowledge and motivation on students’ speaking performance because students’ background knowledge correlated with speaking performance but students’ motivation did not. It was found that the students had good speaking performance and high background knowledge, but low motivation. The students are recommended to gain background knowledge of related consistently so they can have many ideas to talk and can elaborate the ideas. The lecturer is suggested to provide enough background knowledge consistently and notice other factors that affect on students’ speaking performance. However, this study is expected to be developed by future researchers who have the similar field.Key Words: Background Knowledge, Motivation, Speaking Performance